(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
In order to investigate the possibility to increase the efficiency of a flat-plate solar collector the mathematical model of the collector has been worked out. By solving the Laplace heat transfer equation at the boundary conditions accordingly to the construction of the collector, the obtained solution gives possibility to simulate on a computer the construction of the collector in dependence on physical, thermal and economic values of materials used for the construction. The computed results by theoretical formulas with experimental results obtained on special laboratory equipment have been compared and good concurrence acquired.